2016
DOI: 10.1007/s00125-016-4155-5
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal protein septin 11 is associated with human obesity and is involved in adipocyte lipid storage and metabolism

Abstract: Our findings support a role for SEPT11 in lipid traffic and metabolism in adipocytes and open new avenues for research on the control of lipid storage in obesity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 47 publications
2
32
0
4
Order By: Relevance
“…Furthermore, septin-11 was found to be expressed in human adipocytes and upregulated in obese individuals. SEPT11 mRNA was positively correlated with markers of insulin resistance in adipose tissue, and silencing of septin-11 muted insulin signaling and insulin-induced lipid accumulation in adipocytes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, septin-11 was found to be expressed in human adipocytes and upregulated in obese individuals. SEPT11 mRNA was positively correlated with markers of insulin resistance in adipose tissue, and silencing of septin-11 muted insulin signaling and insulin-induced lipid accumulation in adipocytes [40].…”
Section: Discussionmentioning
confidence: 99%
“…3T3‐L1 cells [American Type Culture Collection (Manassas, VA, USA)] were differentiated into adipocytes as previously described 22,26 . Briefly, 3T3‐L1 cells were cultured onto 6‐ or 12‐well plates (3 × 10 3 cells/cm 2 ) or glass coverslips (2 × 10 3 cells/cm 2 ) in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% of newborn calf serum, 4 mM of glutamine, and 1% of antibiotic‐antimycotic solution.…”
Section: Methodsmentioning
confidence: 99%
“…We further examine the association of NECC2 with CAV1 by co‐immunoprecipitation analysis, which revealed the interaction between these two proteins (Figure A and Figure ). However, when we employed a detergent‐free method to isolate caveolin‐enriched membrane fractions, we found that endogenous NECC2, at least the variant identified by the anti‐NECC2 antibody employed herein, did not co‐migrate with CAV1, Cavin1 or IR to “buoyant” fractions (Figure B). Notably, the Na 2 CO 3 lysis buffer employed in this protocol for protein isolation maintains integral but not soluble and peripheral membrane proteins .…”
Section: Resultsmentioning
confidence: 88%
“…A standard protocol was used for co‐immunoprecipitation of NECC2 and CAV1 in HEK‐293 AD cells transfected with c‐Myc‐ Necc2 and CFP‐ Cav1 as described previously …”
Section: Methodsmentioning
confidence: 99%